Metode Pendidikan Influentif Untuk Anak Usia Dini Perspektif Abdullah Nashih Ulwan - Hasan, Subri; Alimah, Nurul (LENTERNAL: Learning and Teaching Journal, 2023)
The focus of this study is to learn about the influential educational methods for early childhood from Abdullah Nashih Ulwan's perspective, as well as their relevance and significance to early children's education today. The type of research is library research using the method of content analysis, but its approach is interpretative and qualitative-descriptive. The main source of this study is the writings of Abdullah Nashih Ulwan on the education of children in Islam. The results of the study show that there are 5 methods of influential education for early childhood based on the perspective of Abdullah nashih ulwan among them: the method of compatibility, the method of cultivation, the method of counseling, the approach of attention or supervision, and the method of punishment. As for the relevance of these five methods, although they were introduced 50 years ago, they are still very relevant to early childhood education today, at the age of 4.0. The significance of these methods is summarized in the three values of education: academic values, religious values, and moral values.